Effect of hydrocortisone on the reactivity of thymus and spleen cells of mice to in vitro stimulation - Vischer, T. L. (1972)
Treatment of mice with hydrocortisone reduced the number of thymus-cells to 6 per cent and the number of spleen-cells to 32 per cent of matched controls. Per spleen, an absolute decrease of cells carrying immunoglobulin receptors on the surface as determined by immunofluorescence was found and a smaller decrease in cells with theta-antigen. Equal numbers of thymus and spleen cells from hydrocortisone-treated mice and matched controls were cultured and stimulated with phytohaemagglutinin (PHA), pokeweed mitogen (PWM), allogeneic cells, and, following immunization, with keyhole limpet haemocyanin (KLH). Stimulation was assessed by incorporation of [(3)H]thymidine into the acid precipitable fraction of the cultured cells. With thymus cells, hydrocortisone treatment increased the reaction to PHA and allogeneic cells. Thymus cells from untreated animals already gave a good response to PWM, further increased by treatment with hydrocortisone. With spleen cells, hydrocortisone treatment reduced the reaction to KLH, PWM, allogeneic cells and PHA in decreasing order. The results are discussed with reference to cells affected by hydrocortisone treatment and to the mechanism of in vitro lymphocyte stimulation.